Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

A molecularly tailored interphase enabling high-efficiency and dendrite-free Zn metal anodes - Yanting Zhou; Yingxin Wu; Donghui Cai; Xiaoyan Lin; Siyuan Shao; Dongze Li; Ziqi Wang (Chemical Engineering Journal, 2026)

Unraveling the biocontrol efficacy and underlying mechanism of Streptomyces rhizosphaerihabitans against postharvest anthracnose caused by Colletotrichum truncatum - Niuniu Shi; Zenghong Luo; Houjun Tian; Nan Zhang; Jiehuang Gao; Yanting Lin; Xuefang Zheng; Benjin Li; Yixin Du (Postharvest Biology and Technology, 2026)

Pollution characteristics and health effects of vehicle emissions particulate matter in undersea tunnel - Anqi Hou; Lingjun Li; Ziyi Lin; Mengren Li; Xiaolong Fan; Xiaohe Wu; Yanting Chen; Lingling Xu; Jinsheng Chen (Journal of Environmental Sciences, 2026)

Engineering Zn2+ solvation and deposition via a ZrBTB-SO3@SPEEK composite polymer separator for high-performance aqueous Zn-ion batteries - Xiaoyan Lin; Siyuan Shao; Dongze Li; Yingxin Wu; Yanting Zhou; Donghui Cai; Ziqi Wang (Chemical Engineering Journal, 2026)

Regulating reversible Zn anodes through a functionalized metal-organic polyhedra interphase for high-performance Zn-ion batteries - Yingxin Wu; Donghui Cai; Yanting Zhou; Xiaoyan Lin; Siyuan Shao; Dongze Li; Ziqi Wang (Chemical Engineering Journal, 2026)

Advancements in environmental microplastic removal and upcycling techniques - Tianyu Lin; Penggang Li; Huaping Jia; Heng Jiang; Fengjia Xie; Yanting Liu; James Kar-Hei Fang; Changchao Li; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Stabilizing photogranule systems under low-light and limited-aeration: From operational strategy to underlying mechanism - Xiaojing Yang; Lan Tang; Jinke Sun; Fahui Ji; Peng Qi; Meng Yan; Yanjuan Luo; Chen Yang; Yanting Lin; Hui Lu (Water Research, 2026)

Combustion and explosion reaction kinetics of thermal runaway gases from three lithium-ion batteries with different metal-oxide cathodes - Song Lin; Yanting Cao; Yunhao Li; Kai Zheng; Yan Tang; Juncheng Jiang (Fuel, 2026)

Enhanced spring precipitation in central Asia induced by ENSO under global warming - Lin Sun; Yanting Zhang; Xiao-Tong Zheng (Climate Dynamics, 2026)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Regulating a P-rich SEI via a phosphoryl MOF-based quasi-solid electrolyte for dendrite-free Li metal batteries - Dongze Li; Siyuan Shao; Xiaoyan Lin; Kun Yao; Shaoru Chen; Donghui Cai; Yingxin Wu; Yanting Zhou; Ruiqi Li; Ziqi Wang (Chemical Engineering Journal, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Application and analysis of two-stage heat recovery and flash vaporization process in high-temperature heat pump systems for steam production - Zheng Huang; Yanting Zhang; Lin Wang; Yunlong Zheng; Guanxiang Qiao (International Journal of Refrigeration, 2025)

Layered sulfonate MOF-functionalized Zn anodes for highly reversible Zn-ion batteries - Xiaoyan Lin; Yiting Lin; Siyuan Shao; Dongze Li; Yingxin Wu; Yanting Zhou; Donghui Cai; Ziqi Wang (Chemical Engineering Journal, 2025)

Genome-resolved metagenomic analysis reveals a novel denitrifier with truncated nitrite reduction pathway from the genus SC-I-84 - Jiapeng Li; Xiaotian Zuo; Qianqian Chen; Yanting Lin; Fangang Meng (Water Research, 2025)

Enhancing the sensitivity of Co-doped LaFeO3 thick-film sensors for low-concentration CO2 detection: Investigating the synergistic effect of complex defects and adsorbed oxygen - Xiaohong Su; Haotian Shan; Yanting Tian; Wei Guo; Peng Zhao; Lin Xue; Yongjia Zhang (Journal of Environmental Chemical Engineering, 2025)

OncomiR mdv1-miR-M7-5p promotes avian lymphomatosis by modulating the BCL2/Bax mitochondrial apoptosis signaling pathway - Jun Zhou; Fan Yang; Congsen Zheng; Yanting Chen; Meiting Chen; Qiaoer Lin; Chuanzhe Chang; Shikai Cai; Zhaoyang Sun; Hua Li; Limei Qin; Yanfeng Chen (Veterinary Microbiology, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

MaERF9 and MaERF113 transcription factors involve in chilling injury development by regulating membrane lipid metabolism of postharvest banana fruit - Lijuan Bai; Yanting Wu; Hetong Lin; Wenbing Su; Zhongqi Fan (Postharvest Biology and Technology, 2025)

Fetal agenesis of corpus callosum: chromosomal copy number abnormalities and postnatal follow-up - Meiying Cai; Na Lin; Meimei Fu; Yanting Que; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2024)
Objective Agenesis of the corpus callosum (ACC) is an anomaly that can occur in fetuses during pregnancy. However, there is currently no treatment for fetal ACC. Therefore, we conducted a retrospective analysis of obstetric outcomes of fetal ACC to explore the relationship between fetal ACC phenotypes and chromosomal copy number abnormalities. Methods and results Amniotic fluid or umbilical cord blood were extracted from pregnant women with fetal ACC for karyotype analysis and chromosomal microarray analysis (CMA). Among the 48 fetuses with ACC, 22 (45.8%, 22/48) had isolated ACC, and 26 (54.2%, 26/48) had non-isolated ACC. Chromosomal abnormalities were detected via karyotype analysis in four cases. In addition to the four cases of pathogenic copy number variations (CNVs) detected using karyotype analysis, CMA revealed two cases of pathogenic CNVs with 17q12 microduplication and 16p12.2 microdeletion. The obstetric outcomes of 26 patients with non-isolated ACC were followed up, and 17 chose to terminate the pregnancy. In addition, seven of the nine cases with non-isolated ACC showed no obvious abnormality during postnatal follow-up, whereas only one case with normal CMA showed an abnormal phenotype at six months. Of the 22 patients with isolated ACC, six chose to terminate the pregnancy. Postnatal follow-up of 16 isolated ACC cases revealed only one with benign CNV, presenting with intellectual disability. Conclusion Pregnant women with fetal ACC should be offered prenatal CMA, particularly non-isolated ACC. Patients with ACC should undergo prolonged postnatal follow-up, and appropriate intervention should be provided if necessary.

The response of surface sedimental diatoms to the environment and its potential significance in the Taiwan Strait, western Pacific - Min Chen; Xuan Liu; Shuqin Tao; Aijun Wang; Yanting Lin; Zhaohe Luo; Ya Xu; Jiayu Li; Qing Huang (Acta Oceanologica Sinica, 2024)

Association Between the Serum Copper Levels and Environmental Tobacco Exposure on the Risk of Overweight and Obesity in Children: a Study Based on the National Health and Nutrition Examination Survey - Yujun Luo; Linzhu Zhang; Yanting Lu; Xiaohong Lin; Zelin Weng; Youjia Xu (Biological Trace Element Research, 2024)

Weak magnetic field promotes denitrification by stimulating ferromagnetic ion-containing metalloprotein expression - Yuan Lin; Yanting Chen; Haiyue Wang; Yuexin Yu; Yanru Wang; Sijia Ma; Laichun Wang; Hongqiang Ren; Ke Xu (Water Research, 2024)

Diesel exhaust exposure induced squamous metaplasia of corneal epithelium via yes-associated protein activation - Xiaoya Ji; Yanting Li; Meike Liu; Linfei Chen; Xinglin Zhang; Mingyue Wang; Shuhan Tian; Lin Lu; Mingliang Zhang; Yuxin Zheng; Jinglong Tang (Chemosphere, 2024)

Activation energy and organic matter structure characteristics of shale kerogen and their significance for the in-situ conversion process of shale oil - Wenxue Han; Xia Luo; Shizhen Tao; Senhu Lin; Jinzhong Liu; Yanting Yang (Fuel, 2024)

Microplastics reduce trace metal bioavailability in Thalassiosira weissflogii by impairing physiological functions - Yanting Du; Qianyan Huang; Shunxing Li; Minggang Cai; Fengjiao Liu; Xuguang Huang; Luxiu Lin; Fengying Zheng; Weijun Chen; Ying Yang (Marine Chemistry, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Decoding the Puzzle of Late Ediacaran Glaciation(s) - Bin Wen; Yanting Lin; Fuyun Shen; Junyuan Zhou (Journal of Earth Science, 2024)

Performance and mechanistic studies of rapid atenolol degradation through peroxymonosulfate activation by V, Co, and bamboo carbon catalyst - Yihui Hu; Kai Yang; Yule Lin; Xin Weng; Yanting Jiang; Jian Huang; Yuancai Lv; Xiaojuan Li; Yifan Liu; Chunxiang Lin; Minghua Liu (Environmental Science and Pollution Research, 2024)

Dissolved organic matter accelerates microbial degradation of 17 alpha-ethinylestradiol in the presence of iron mineral - Huan He; Min Shi; Xiaoxia Yang; Juhong Zhan; Yanting Lin; Ziwei Guo; Zhicheng Liao; Chaochao Lai; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

Carbon sequestration reduced by the interference of nanoplastics on copper bioavailability - Yanting Du; Qianyan Huang; Shunxing Li; Minggang Cai; Fengjiao Liu; Xuguang Huang; Fengying Zheng; Luxiu Lin (Journal of Hazardous Materials, 2024)

Enhanced peroxymonosulfate (PMS) activation process mediated by vanadium modified CoO catalyst for rapid degradation of organic pollutants: Insights into the role of V - Yanting Jiang; Xin Weng; Yihui Hu; Yuancai Lv; Zhendong Yu; Yifan Liu; Xiaojuan Li; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2024)

Sources appointment and health risks of PM2.5-bound trace elements in a coastal city of southeastern China - Ziyi Lin; Xiaolong Fan; Gaojie Chen; Youwei Hong; Mengren Li; Lingling Xu; Baoye Hu; Chen Yang; Yanting Chen; Zhiqian Shao; Jinsheng Chen (Journal of Environmental Sciences, 2024)

Biocontrol activity of an endophytic Alternaria alternata Aa-Lcht against apple Valsa canker - Yanting He; Runze Tian; Chengyu Gao; Lin Ji; Xiao Liu; Hao Feng; Lili Huang (Pesticide Biochemistry and Physiology, 2024)

Regional ship collision risk prediction: An approach based on encoder-decoder LSTM neural network model - Chenyan Lin; Rong Zhen; Yanting Tong; Shenhua Yang; Shengkai Chen (Ocean Engineering, 2024)

Fluorescence detecting glycopeptide antibiotics via a dynamic molecular switch - Xiaomei Zou; Yanting Lin; Shihui Zhang; Tao Deng; Ximing Xu; Yingchun Zhou; Zhihui Liu; Weiguo Lu; Qingzhong Hu; Chaozhan Lin; Chenchen Zhu; Fang Liu (Analytica Chimica Acta, 2024)

Malic acid inhibits accumulation of cadmium, lead, nickel and chromium by down-regulation of OsCESA and up-regulation of OsGLR3 in rice plant - Xin Zhang; Weijie Xue; Lin Qi; Changbo Zhang; Changrong Wang; Yongchun Huang; Yanting Wang; Liangcai Peng; Zhongqi Liu (Environmental Pollution, 2024)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

The interference of marine accidental and persistent petroleum hydrocarbons pollution on primary biomass and trace elements sink - Fengjiao Liu; Qianyan Huang; Yanting Du; Shunxing Li; Minggang Cai; Xuguang Huang; Fengying Zheng; Luxiu Lin (Science of The Total Environment, 2023)

Preparation and study of bark-like MXene based high output power hydroelectric generator - Xiaoyang Zhang; Yanting Wang; Xuefei Zhang; Ching-Wen Lou; Jia-Horng Lin; Ting-Ting Li (Chemical Engineering Journal, 2023)

Identifying gaps in the ex situ conservation of native plant diversity in China - Jianfei Ye; Zhangjian Shan; Danxiao Peng; Miao Sun; Yanting Niu; Yun Liu; Qian Zhang; Yong Yang; Qinwen Lin; Jin Chen; Renbin Zhu; Yingwei Wang; et al. (Biological Conservation, 2023)

Configuration method for combined heat and power plants with flexible electricity regulation - Xiaoyin Wang; Yanting Wu; Lin Fu (Energy and Buildings, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

An epipolythiodioxopiperazine alkaloid and diversified aromatic polyketides with cytotoxicity from the Beibu Gulf coral-derived fungus Emericella nidulans GXIMD 02509 - Miaoping Lin; Zhenzhou Tang; Jiaxi Wang; Humu Lu; Chenwei Wang; Yanting Zhang; Xinming Liu; Chenghai Gao; Yonghong Liu; Xiaowei Luo (Journal of Zhejiang University-SCIENCE B, 2023)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

Top‐down controls on nutrient cycling and population dynamics in a model estuarine photoautotroph–heterotroph co‐culture system - Qiang Zheng; Wenxin Lin; Yu Wang; Dapeng Xu; Yanting Liu; Nianzhi Jiao (Molecular Ecology, 2021)
Viral lysis and protistan grazing are thought to be the major processes leading to microbial mortality in aquatic environments and thus regulate community diversity and biogeochemical cycling characteristics. Here, we studied nutrient cycling and bacterial responses to cyanophage‐mediated photoautotroph lysis and ciliate predation in a model Synechococcus –heterotroph co‐culture system. Both viral lysis and Euplotes grazing facilitated the transformation of organic carbon from biomass to dissolved organic matter with convention efficiencies of 20%–26%. The accumulation of ammonium after the addition of phages and ciliates suggested the importance of recycled NH 4 + occurred in the interactions between Synechococcus growth and heterotrophic bacterial metabolism of photosynthate. The slower efficiency of P mineralization compared to N (primarily ammonium) indicated that P‐containing organic matter was primarily integrated into bacterial biomass rather than being remineralized into inorganic phosphate under C‐rich conditions. In the cyanophage addition treatment, both Fluviicola and Alteromonas exhibited rapid positive responses to Synechococcus lysing, while Marivita exhibited an apparent negative response. Further, the addition of Euplotes altered the incubation system from a Synechococcus ‐driven phycosphere to a ciliate‐remodelled zoosphere that primarily constituted grazing‐resistant bacteria and Euplotes symbionts. Top‐down controls increased co‐culture system diversity and resulted in a preference for free‐living lifestyles of dominant populations, which was accompanied by the transfer of matter and energy. Our results indicate top‐down control was particularly important for organic matter redistribution and inorganic nutrient regeneration between photoautotrophs and heterotrophs, and altered bacterial lifestyles. This study consequently sheds light on marine biogeochemical cycling and the interaction networks within these dynamic ecosystems.

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

Antiplatelet Strategies and Outcomes in Patients with Noncardioembolic Ischemic Stroke from a Real-World Study with a Five-Year Follow-Up - Huimin Xu; Yanting Ping; Haoran Lin; Ping He; Wenlu Li; Haibin Dai (Translational Stroke Research, 2017)

Raltitrexed’s effect on the development of neural tube defects in mice is associated with DNA damage, apoptosis, and proliferation - Yanting Dong; Xiuwei Wang; Jianlin Zhang; Zhen Guan; Lin Xu; Jianhua Wang; Ting Zhang; Bo Niu (Molecular and Cellular Biochemistry, 2015)

Regional differences in the relationship between climatic factors, vegetation, land surface conditions, and dust weather in China’s Beijing-Tianjin Sand Source Region - Jianjun Wu; Lin Zhao; Yanting Zheng; Aifeng Lü (Natural Hazards, 2012)